Bridging chemistry education research and practice through research-practice partnerships - Popova, Maia (Frontiers in Education, 2024)
This perspective article is a call to establish research-practice partnerships (RPPs) to foster collaborations between instructors and education researchers to tune into the needs of practice, share evidence-based practices, and solve modern organic chemistry education problems. I begin the article by discussing some limitations of the traditional approach of "translating" research into practice and suggest RPPs as an alternative model for "bridging" research and practice. Importantly, RPPs have been shown to address persistent problems of practice and improve educational outcomes. While more common at the secondary level, RPPs are rarely leveraged in post-secondary chemistry education. The article goes on to provide a concrete and relevant context for potential future RPP efforts to improve aspects of organic chemistry education-RPPs between education researchers and organic chemistry instructors to work toward designing, administering, and testing interventions to support learners' representational competence (RC). RC is a set of skills that allow for the reflective use of a variety of representations to think about, communicate, and act on chemical phenomena. Current instruction often falls short of effectively supporting learners in developing RC. It is often tacitly assumed that learners will develop RC without explicit instruction that scaffolds the development of the RC skills. While it is important to improve the teaching about and with representations, implementing innovative pedagogical approaches can be challenging, particularly when instructors feel isolated in their efforts within their work environments. The RPP model could catalyze solutions to these challenges by pooling diverse expertise, thus enabling more robust and sustainable educational innovations.